Pembangunan Karakter Generasi Emas : Solusi Komperehensif Permasalahan Perilaku Siswa - Nisa Pratiwi Harahap; Adelia Pratiwi; Siti Chairunnisa; Fitri Handina; Khairunnisa Khairunnisa (Departement of Mathematics Education, 2024)
This study aims to examine comprehensive strategies in character development for the golden generation to address student behavior issues. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The results show that effective character development involves collaboration between family, school, and community. The implementation of systematic and sustainable character education programs has proven to reduce negative student behaviors and enhance their positive attitudes and social skills. This study's recommendations emphasize the importance of training for teachers and parents as well as the integration of character values into the educational curriculum.